PELATIHAN AKUNTANSI PONDOK PESANTREN BERBASIS STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) BAGI PENGELOLA KEUANGAN PONDOK PESANTREN DI KECAMATAN PEMENANG KABUPATEN LOMBOK UTARA NTB - Saipul Arni Muhsyaf; Siti Atikah; Iman Waskito (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2022)
The Islamic boarding school foundation is a non-profit entity that is obliged to compile financial reports as a form of accountability to the stakeholders and most importantly Allah SWT. There are several steps that must be taken by the Islamic boarding school foundation in preparing financial reports. First, the highest leadership of the foundation must make a strong commitment, starting to separate personal wealth from institutional wealth. The next step, the leadership must determine and place the right individual in the right place as an employee in charge of finance. The boarding school can be accompanied by this activity team or by academics in terms of carrying out an inventory of assets and liabilities, followed by measurement and preparation of the initial financial position report.